Understanding the emergence of rural agrotourism: A study of influential factors in Jambi Province, Indonesia - Zulgani Zulgani; Junaidi Junaidi; Dwi Hastuti; Ernan Rustiadi; Andrea Emma Pravitasari; Fadwa Rhogib Asfahani (Economies, 2023)
This investigation delineates the multi-faceted determinants integral to the evolution of agrotourism within rural domains, concentrating on the province of Jambi as a case study. This scholarly inquiry engaged with four representative villages, utilizing primary data procured through focus group discussions (FGDs) and comprehensive interviews with various stakeholders. These encompass village administration, village-owned enterprises (BUMDes), youth organizations, the regional body for planning and development, the tourism office, community figureheads, village facilitators, commercial operators, and local community delegates. The analytical methodology incorporated the transcription of FGDs and comprehensive interviews, data distillation, analytical interpretation, and triangulation. The NVivo 11 Plus suite facilitated this qualitative data analysis. The investigation discerned six cardinal determinants that substantively influence the trajectory of agrotourism development within rural areas. These include the potential of nature tourism, the accessibility, and caliber of agro-products, the adequacy of infrastructure, the involvement and roles of community and institutional bodies, technological innovation, and the safeguarding of local cultural heritage. This scholarly inquiry underscores the necessity of a collaborative approach in formulating and implementing policies. This approach, which calls for the inclusion of diverse stakeholders, is aimed at bolstering the sustainable development of agrotourism.
Keywords: 330; agrotourism; rural; sustainable development